Criminal Liability for Media Alignment in Election Campaigns - Widyawati, Anis; Desiana, Wahyu (Law Research Review Quarterly, 2018)
Elections become the biggest democracy event in Indonesia which not only has an impact on the political and legal aspects, but also social and education. One of the problems in the context of democracy and elections in Indonesia is to support the mainstream media for certain pairs of candidates or parties so that in many cases uneven, biased and tendentious news is found. This paper looks at the form of criminal responsibility for media alignments in the election campaign. Is this form of partiality included in the realm of Criminal Law. This paper looks at various cases that have occurred and compares them.